2024
DOI: 10.3390/su16051773
|View full text |Cite
|
Sign up to set email alerts
|

Multicriteria Analysis of Cement Mortar with Recycled Sand

Maja Kępniak,
Paweł Łukowski

Abstract: Sustainable development requires a holistic perspective that integrates the different aspects of production and consumption and promotes the transition to a circular economy. This approach aims to balance the needs of the present and future generations, as well as the social, environmental, and economic dimensions of development. By producing products that are durable, recyclable, and reusable, and by minimizing the use of energy and materials, the environmental impact of production can be reduced while also g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…The experimental results indicate that the compressive strength at 28 days decreased by 3.37%, 5.09%, 10.82%, 14.09%, 18.91% and 21.16% for the recycled sand replacement rates of 20%, 33.33%, 40%, 60%, 80% and 100%, respectively. The results obtained in this research are consistent with those reported by other authors (Kępniak et al, 2024;Mora-Ortiz et al, 2020).…”
Section: Compressive Strength Testsupporting
confidence: 94%
“…The experimental results indicate that the compressive strength at 28 days decreased by 3.37%, 5.09%, 10.82%, 14.09%, 18.91% and 21.16% for the recycled sand replacement rates of 20%, 33.33%, 40%, 60%, 80% and 100%, respectively. The results obtained in this research are consistent with those reported by other authors (Kępniak et al, 2024;Mora-Ortiz et al, 2020).…”
Section: Compressive Strength Testsupporting
confidence: 94%
“…This innovative approach enhances sustainability in construction by effectively reusing waste, thereby aligning with environmental conservation efforts [17]. Łukowski et al's 2024 research demonstrates that replacing natural sand with recycled sand in cement mortar offers significant environmental and economic benefits without notably affecting its technical properties, thereby promoting sustainability in construction [18]. Conventional concrete, when utilizing brick or recycled brick aggregates, typically exhibits lower mechanical strength and reduced durability than stone aggregates [19,20].…”
Section: Introductionmentioning
confidence: 99%